Ocean-estuarine connection for ichthyoplankton through the inlet channel of a temperate choked coastal lagoon (Argentina) - Bruno, Daniel Osvaldo (2014)
We examined the fish larvae colonising pattern of the Mar Chiquita lagoon (Argentina).We hypothesised that in this microtidal lagoon, winds could regulate fish larvae dynamics. Ichthyoplankton samples were taken in marine waters, the surf zone and the estuary. Previous studies showed no reproduction by fishes with planktonic eggs inside the lagoon. However high abundance of eggs and larvae of Brevoortia aurea collected within the estuary also suggest possible spawning activity. Throughout the study period, the cumulated richness of fish larvae was slightly higher in the estuary. However, univariate analysis revealed a higher number of species per tow in marine waters than in the estuary. The lowest average values of fish density, number of species and diversity recorded in the surf zone suggest that this area is only used as a transient corridor between the sea and the lagoon. The canonical correspondence analysis (CCA) indicated that wind direction, tidal stage, temperature and rainfall contributed significantly to the fish larvae distribution patterns observed; being ?onshore wind? the most important variable affecting fishes. Our results show how winds, in addition to pushing seawater into the lagoon, contribute to larvae recruitment into this estuary. Finally, we discuss the role of small lagoons in the life-history of coastal fishes.